The effects of impact forces and kinematics of two different stance at straight punch techniques in boxing - Meric Bingul, B.; Bulgan, C.; Tore, O.; Aydin, M.; Bal, E. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: The punch is a key component of boxing. In scientific papers there are informations about kinematic indicators and impact forces. It mentioned that lower extremity have a strong effect on impact force, through transferring momentum into the kinetic chain system. However, the differences of impact forces in different boxing posture have not been fully investigated. The aim of the study was the effects of impact forces and some kinematic indicators in boxing both orthodox and southpaw stance of straight punch technique.